Respuesta :

Answer:

3

Step-by-step explanation:

3

(

2

+

5

)

=

7

(

2

1

0

)

+

5

{\color{#c92786}{3(2x+5)}}=-7(2x-10)+5

3(2x+5)=−7(2x−10)+5

6

+

1

5

=

7

(

2

1

0

)

+

5

⁺˚*・༓☾✧.* ☽༓・*˚⁺‧

[tex]\huge\boxed{\boxed{\underline{\textsf{\textbf{Answer}}}}}[/tex]

[tex]3(2x + 5) = - 7(2x - 10) + 5 \\ 6x + 15 = - 14x + 70 + 5 \\ 6x + 14x = 70 + 5 - 15 \\ 20x = 75 - 15 \\ 20x = 60 \\ x = \frac{60}{20} \\ x = 3[/tex]

⁺˚*・༓☾✧.* ☽༓・*˚⁺‧

____________________

ʰᵒᵖᵉ ⁱᵗ ʰᵉˡᵖˢ

꧁❣ ʀᴀɪɴʙᴏᴡˢᵃˡᵗ2²2² ࿐